Correlation of Vitamin D Serum Levels with Muscle Mass, Muscle Strength, and Physical Performance in the Elderly Community in Mohammad Hoesin General Hospital Palembang - Noveldy Calzoum Bachry; Nur Riviati; Yulianto kusnadi; Erial Bahar (HM Publisher, 2021)
Background: Older people tend to have decreased activity and intake of macronutrients and micronutrients that are not in accordance with the body's needs. Research in 2017 on elderly men and women at the Center for Family Compensation (PUSAKA) in Central Jakarta showed that 80.2% of elderly people have vitamin D deficiency. Low serum levels of vitamin D in the body are the initial risk of decreased muscle mass and physical performance in old age. where there is a significant correlation between low serum vitamin D levels in the body with sarcopenia and mortality. The purpose of this study was to determine the correlation of vitamin D levels with muscle mass, muscle strength and physical performance in the elderly community at RSMH Palembang. Methods: This research is a study analytic observation with a cross-sectional approach that was carried out at the Integrated Geriatric Clinic Internal Medicine RSMH Palembang from November 2019 to November 2020. A sample of 34 people aged> 60 years were examined for muscle mass, muscle strength, physical performance and serum vitamin D levels. All processing and analysis The data in this study used SPSS version 25 for Windows. Results: From 34 subjects, it was found that there were 29 women (85.3%) and 5 men (14.7%). The mean value of muscle mass is38.76 ± 4.1 kg / m2, long runs within 6 meters 6.12± 0.9 m / sec, and hand grip strength 24.9 ± 5.2 kg. It was found that 18 (62.1%) female samples had vitamin D deficiency while 11 (37.9%) samples had vitamin D insufficiency. There was a significant correlation between muscle mass and hand grip strength with vitamin D with weak correlation strength and length of walking with vitamin D with moderate correlation strength. Conclusion: There is a significant correlation between muscle mass and grip strength and walking time of 6 meters with vitamin D.